Desenhando n(o) Conflito: o papel do projeto na representação das demandas espaciais da cidade informal - De Boni, Juliana (2023)
In Brazil, the State is often perceived as a promoter of official Urban Planning (Souza, 2006). The transformation project of urban space, as one of the outcomes of such planning, should be capable of translating local demands and be integrated with the interdisciplinary nature required by the planning process. Given the formation of Brazilian cities under a deeply rooted policy of patrimonialist, clientelist, and colonial relations (Schwarcz, 2019), the urban planning offered by the State produces and reproduces socio-spatial inequality, catering to the interests of more privileged groups. With the crisis of modern capitalism and the rise of the democratic model alongside neoliberalism, a wave of social movements advocating for the right to the city emerges, demonstrating that citizenship in contemporary times is established through daily resistance to the hegemonic model that invisibilizes, privatizes, and excludes (Miraftab, 2012). Viewed through Vainer's perspective (2016), where the city is an arena of conflicts, and understanding the project as a visualization of the execution of the proposed planning that can permeate both the institutional and opposition spheres, the research question of this work revolves around the analysis of the project and its interfaces—the design—as a tool for claiming and negotiating rights through the study of alternative planning practices in Fortaleza. With the aim of investigating the importance of the project as a tool for negotiating rights and the potentiality of designing with and for communities in vulnerable situations, this work is divided into three parts. The first part concerns the construction of the state of the art of this research. It focuses on important theoretical definitions regarding planning theory, the conflict perspective, citizenship, and participation, initiating the discussion on the project and design. It presents an investigation into projects outside the institutional apparatus, selecting a repertoire of 15 alternative planning practices in Brazil that involve the development of projects and plans capable of questioning and modifying the current order. The second part comprises the contextualization of the empirical object of the research, incorporating different geographic scales of analysis and investigating the layers surrounding the hegemonic project in the studied conflict. The third and final part of this work translates into action research on the conflict in the Saporé community. It arises as an attempt to explore the potential of the project and its layers, involving analyses from the confrontation between the official project, which obscures many dimensions, and the intention to map the community's reality to make residents see themselves in space, finally feeling seen and part of the city. This extends to the construction of an alternative resettlement plan.